Retroperitoneal PEcoma (angiomyolipoma) composed exclusively of epithelioid lipoblastic-like cells: a diagnostic conundrum on needle biopsy. Issue 3 (March 2016) - Cheung, Carol C.; Kalimuthu, Sangeetha N.; Chetty, Runjan
Abstract: Angiomyolipomas are one of several distinct entities that belong to the "PEComa" (perivascular epithelioid cell tumour) family that comprise varying degrees of fatty, smooth muscle and vascular components. Angiomyolipomas occurring in the retroperitoneum are relatively uncommon; however, when all of the three components are represented, the diagnosis can be readily made. Herein, we report the first case of a retroperitoneal angiomyolipoma composed exclusively of epithelioid and lipoblast-like cells. An extra-renal retroperitoneal mass was biopsied and revealed a relatively uniform population of epithelioid cells arranged in sheets separated by both a delicate vascular network and vessels of larger calibre. The tumour cells were small to medium in size with mild nuclear pleomorphism and cytoplasmic vacuolization ranging from multiple large vacuoles to larger vacuoles, resembling lipoblasts. Occasional nuclei were seen to have prominent clear nuclear pseudo-inclusions. Immunohistochemistry revealed the cells to be strongly positive for SMA and focally positive for HMB45, MiTF and S100. The tumour cells were negative for AE1/AE3, CAM5.2, CD45, Pax8, SF-1 and TFE3. Angiomyolipomas in the retroperitoneum share morphological similarities with a wide variety of tumours, chiefly liposarcoma. Awareness of angiomyolipomas composed purely of epithelioid and lipoblast-like cells is essential to avoid misdiagnoses.